PEMBIASAAN HABITUASI KEGIATAN RELIGIUS DALAM PEMBENTUKAN KECERDASAN SPIRITUAL SISWA DI MI MIFTAHUL ULUM SUMBERREJO - Jamhuri; Siti Maisaroh (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Education is a conscious effort by the government, through guidance, teaching and training activities, which take place at school and outside of school for life, to prepare students to be able to play a role in a variety of environments precisely in the future. Various problems such as social change that is so large affect the attitude and behavior of a person. So that often seen damage to human behavior that occurs at this time in social and social life, such as lack of courtesy and good behavior in the family and community. For this reason, MI Miftahul Ulum Sumberrejo organizes religious activities that aim to make students familiar with religious activities and have good morals and behavior towards others. This study aims to describe the habituation of religious activities and habituation of religious activities in the formation of student intelligence at MI Miftahul Ulum Sumberrejo. This study uses a qualitative approach in this study, data collection techniques used are observation, interviews, and documentation. Data analysis techniques used in this study are data reduction, data presentation, drawing conclusions or verification. The results of this study indicate that: 1) religious activities in MI Miftahul Ulum Sumberrejo include; perform duha prayer, perform dzuhur prayers in congregation and read short letters, 2) Habituation of religious activities in the formation of students' spiritual intelligence, namely the teacher starts by saying good words, wearing polite clothes and teaching his students to always have a good personality, always be thankful for what you have, have an honest attitude. The formation of spiritual intelligence through religious activities, the school seeks to increase the potential of students to the maximum and also the level of spirituality of students can be embedded in students. While the method used in this activity is the habituation method.